Customer Satisfaction in Libraries - Sridhar, M.S. (Journal of Information and Knowledge, 2022)
The paper points out certain quantitative methods largely ignored by library service providers; Highlights the importance of customer participation in service delivery process; Examines the concepts ‘service quality’ and ‘customer satisfaction’; emphasizes the need for appropriately handling waiting lines in service organizations; presents briefly the theory of waiting lines (queueing theory), psychology of customers in waiting lines with illustrations from library situations; Discusses ways and means of reducing delays in waiting lines and increasing service quality and customer satisfaction and concludes by stressing the need for appropriate studies on these lines in Librarianship.